Utility of scrape cytology in the diagnosis of ovarian masses - Ghosh, Sanchita; Jain, Bhawna Bhutoria; Nandi, Ayandip; Banerjee, Uma (International Journal of Research in Medical Sciences, 2019)
Background: Cytology is a useful adjunct to frozen section for rapid diagnosis of neoplastic pathology. However frozen section facility is available in limited centres. Therefore, we undertook this study to find out role of scrape cytology for diagnosis of ovarian masses. Methods: It is an observational study done in a medical college. One hundred ovarian masses were collected for a period of eighteen months. Cut surface of ovarian masses were scraped with edge of a glass slide. Smears were prepared and stained with H and E stain, examined and a presumptive diagnosis was given. The verification of cytological diagnosis was done by histopathological report. All the data were recorded, tabulated and analyzed with the help of standard statistical methods using Microsoft XL. Results: A total of hundred cases were studied. Left ovary was involved in 38 cases, right ovary in 52 cases and bilateral ovaries in 10 cases. Malignant cases mostly yielded hyper cellular smear. On Chi square test, it was significant with value of less than .001. The overall sensitivity and specificity of scrape cytology in diagnosing ovarian neoplasm, considering HPE as gold standard, are 98% and 78% respectively. In Dysgerminoma, Papillary adenocarcinoma, Mucinous Cystadenoma, Benign cystic teratoma, Granulomatous lesion of ovary, Lymphoma and Mucinous adenocarcinoma, scrape diagnosis corroborated with the histological diagnosis. Notable discrepancy was seen in cases of Endometrioid carcinoma. Conclusions: Scrape cytology can serve as a powerful tool for early diagnosis of ovarian masses in close cooperation of the clinician, radiologist and pathologist. It has a potential for widespread use as knowledge and experience of interpreting cytopathologists increase.